Isolated splenic tuberculosis in a patient with rheumatoid arthritis - Yuji Toyota; Akihiro Ito; Tadashi Ishida (IDCases, 2025)
Isolated splenic tuberculosis (TB) is rare. Here, we report a case of isolated splenic TB in a 70-year-old man with rheumatoid arthritis (RA). The patient presented to the emergency department with a 3-day history of epigastric pain and hematemesis. For RA treatment, a combination of methotrexate (8 mg) and baricitinib (4 mg) had been initiated 2 years prior. Abdominal computed tomography (CT) scan revealed upper gastrointestinal hemorrhage and intrasplenic involvement. Following endoscopic hemostasis, we performed endoscopic ultrasound-guided fine-needle aspiration via the stomach due to suspected pancreatic cancer. At an outpatient follow-up visit 1 month later, fever and elevated C-reactive protein (9.02 mg/dL) levels were observed. CT imaging showed enlarged necrotic lymph nodes near the gastroesophageal junction, left mesentery of the colon, and the greater curvature of the pylorus, along with an increased low-density area in the spleen. Subsequently, upper gastrointestinal endoscopy and ultrasound-guided percutaneous fine-needle aspiration cytology were performed. Cultures from the abscesses tested positive for Mycobacterium tuberculosis, which was susceptible to isoniazid, rifampicin, ethambutol, and pyrazinamide. No lesions were identified, thus confirming a diagnosis of isolated splenic TB. Oral anti-TB treatment with four drugs (isoniazid, rifampicin, ethambutol, and pyrazinamide) was initiated. After 6 months of treatment, the splenic lesions had shrunk. Nine months after completing therapy, RA treatment was resumed without relapse. Therefore, early diagnosis and anti-TB treatment can successfully manage splenic TB without requiring splenectomy.